2016
DOI: 10.1007/s13277-016-5180-1
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CXCR7 inhibits proliferative capacity and stem cell-like properties in breast cancer stem cells

Abstract: Breast cancer stem cells (bCSCs) are considered an obstacle in breast cancer therapy because they exhibit long-term proliferative potential, phenotypic plasticity and high resistance to the current therapeutics. CXC chemokine receptor type 7 (CXCR7), which provides a growth advantage to breast cancer cells, has recently been demonstrated to play an important role in the maintenance of stem cell-like properties in the CSCs of glioblastoma and lung cancer, yet its role in bCSCs remains elusive. In this study, CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…3, these cells expressed relatively high levels of CXCR4 and CXCR7 compared to NMVP and HMVP1 cells. In further support of this hypothesis, Dubrovska et al reported that in human PCa cell lines (DU145 and PC3), CXCR4 expression was elevated in the CD44 + /CD133 + subpopulation of cells and that these cells were considerably more tumorigenic [57] and recent evidence suggests that CXCR7 is involved in maintaining the stem like properties of breast, glioblastoma and lung cancer cells [5860]. …”
Section: Discussionmentioning
confidence: 99%
“…3, these cells expressed relatively high levels of CXCR4 and CXCR7 compared to NMVP and HMVP1 cells. In further support of this hypothesis, Dubrovska et al reported that in human PCa cell lines (DU145 and PC3), CXCR4 expression was elevated in the CD44 + /CD133 + subpopulation of cells and that these cells were considerably more tumorigenic [57] and recent evidence suggests that CXCR7 is involved in maintaining the stem like properties of breast, glioblastoma and lung cancer cells [5860]. …”
Section: Discussionmentioning
confidence: 99%
“…An important driver of chemokine gradients in the tumor microenvironment are cancer cells under aerobic glycolysis, which produce lactic acid that activates NF-κB and induces CXCL8 expression in vascular endothelial cells, resulting in angiogenesis in breast and colon cancer (20, 21). CXCL8 also upregulates CXCR7/ACKR3, which is involved in stemness features of cancer cells suggesting it is also likely involved in EPC mobilization (2224).…”
Section: Introductionmentioning
confidence: 99%
“…CXCR7/RDC1 receptor is expressed by immune, endothelial, and tumor cells and binds SDF-1 with high affinity [28]. Although CXCR7 was thought to act as a scavenger receptor [29], it was recently demonstrated that SDF-1/CXCR7 signaling induces CSC proliferation/survival and EMT [30, 31], supporting growth and metastasis in different tumor types.…”
Section: Introductionmentioning
confidence: 99%